EXPLANATION OF VOCATIONAL MUHKAM MUTASYABIH AND THE EXISTENCE OF MUHKAM WA MUTASYABIH - Nisa Nurzanah; Hasbiyallah Hasbiyallah; Maslani Maslani (State Institute of Islamic Studies (IAIN) Palu, 2019)
We as Muslims are inseparable from the learning of the Holy Qur'an, because the Qur'an is the first and foremost source and legal basis. Therefore, the Qur'an is from various aspects. In reading the Koran there is also a verse called muhkam and mutasyabih. This research method uses a literature study, the author reads references from several literations, which are finally made as additional knowledge for the author. Wisdom verse muhkam means to facilitate the knowledge and purpose of the verse so that it is easy to practice the implementation of its teachings. The wisdom of the verse Mutasyabih is to add merit, because with so many verses it requires help and effort in expressing its intentions.